Assessing The Succes of Flood and Tidal Flood Control Infrastructure Program in Semarang: A Community Perspective - Putri, Shinta Permana (Jayapangus Press, 2025)
This research aims to assess the success of the flood and tidal flood control infrastructure program in Semarang City based on the perspective of the affected community. The assessment is based on five criteria namely effectiveness, sustainability, responsiveness, alignment with planning, and community involvement. This research uses a quantitative approach. Data was collected through a questionnaire survey of 200 affected communities. A number of samples were collected with stratified sampling techniques based on each drainage system coverage area in Semarang City. The scoring analysis technique was used to assess the program’s success. The result of this study indicates that the development of flood and tidal flood control infrastructure in Semarang City is considered largely unsuccessful with four criteria considered less successful and one unsuccessful. These results highlight the need for improvements in program implementation. This study can be used as a reference for the Semarang City Government to improve the flood and tidal flood control infrastructure development program.